2000
DOI: 10.1042/bj3510509
|View full text |Cite
|
Sign up to set email alerts
|

Purified recombinant insulin-degrading enzyme degrades amyloid β-protein but does not promote its oligomerization

Abstract: Amyloid beta-protein (Abeta) has been implicated as an early and essential factor in the pathogenesis of Alzheimer's disease. Although its cellular production has been studied extensively, little is known about Abeta clearance. Recently, insulin-degrading enzyme (IDE), a 110-kDa metalloendopeptidase, was found to degrade both endogenously secreted and synthetic Abeta peptides. Surprisingly, IDE-mediated proteolysis of [(125)I]Abeta(1-40) in microglial cell-culture media was accompanied by the formation of (125… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
24
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(28 citation statements)
references
References 44 publications
(249 reference statements)
4
24
0
Order By: Relevance
“…The present investigation in both in vitro and in vivo models revealed that 17β-E2 rapidly increased brain IDE protein levels after a 12 to 48-h treatment. A number of recent studies indicate that IDE cleaves APP-derived peptides including Aβ and APP intracellular domain at multiple sites and that the velocity of the reaction is extremely high (Chesneau, et al, 2000; Edbauer, et al, 2002; Mukherjee, et al, 2000). For instance, in an in vitro experiment, purified recombinant wild-type human IDE degraded about 75% of Aβ following just a 1-h co-incubation (Chesneau, et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The present investigation in both in vitro and in vivo models revealed that 17β-E2 rapidly increased brain IDE protein levels after a 12 to 48-h treatment. A number of recent studies indicate that IDE cleaves APP-derived peptides including Aβ and APP intracellular domain at multiple sites and that the velocity of the reaction is extremely high (Chesneau, et al, 2000; Edbauer, et al, 2002; Mukherjee, et al, 2000). For instance, in an in vitro experiment, purified recombinant wild-type human IDE degraded about 75% of Aβ following just a 1-h co-incubation (Chesneau, et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…A number of recent studies indicate that IDE cleaves APP-derived peptides including Aβ and APP intracellular domain at multiple sites and that the velocity of the reaction is extremely high (Chesneau, et al, 2000; Edbauer, et al, 2002; Mukherjee, et al, 2000). For instance, in an in vitro experiment, purified recombinant wild-type human IDE degraded about 75% of Aβ following just a 1-h co-incubation (Chesneau, et al, 2000). These findings suggest again the significance of the role played by estrogen on brain IDE, and such a role could serve as a key contributory mechanism underlying estrogen-mediated prevention of AD.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to increased processing of APP by GSK3, the accumulation of soluble and insoluble Aβ in the diabetic-APP transgenic mice brain may result from reduced degradation. The Insulin-Degrading Enzyme (IDE) degrades insulin but also a number of other small proteins, including Aβ (Chesneau, et al, 2000). IDE protein levels and activity are reduced in AD brains (Perez, et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…1998) and a wide range of evidence now supports its role in this regard from studies in vitro through cell‐based and animal models (e.g. Chesneau et al. 2000; Farris et al.…”
Section: Insulin‐degrading Enzyme (Insulysin Ide)mentioning
confidence: 99%